2013
DOI: 10.21608/zumj.2013.4277
|View full text |Cite
|
Sign up to set email alerts
|

An Interventional Study to Decrease Central Venous Catheter Related Blood Stream Infection in Intensive Care Units at Zagazig University Hospital

Abstract: Background: Catheter related blood stream infection (CRBSI) is a complication of central venous catheter (CVC) use. This Infection particularly in the ICU population results in higher levels of morbidity and mortality coupled with greater costs in terms of care and increased duration of hospital stay. Aim & Objectives: The aim of this study is to improve the safety of patients with CVC via decreasing the incidence of CRBSI in ICUs patients at Zagazig University Hospital through the following objectives: 1-Calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…The mean knowledge score for CRBSI prevention guidelines was very low for both nurses and physicians, although there was a significant difference in their mean scores with nurses performing better than physicians. This result contradicts the results of two studies conducted in Egypt, 12,30 which found low levels of knowledge for both physicians and nurses but with no significant difference between them. The explanation for this result might be that the nurses play an essential role in the daily care of CVC patients, while physicians are confined to CVC insertion in our selected hospitals.…”
Section: Differences In the Knowledge Level Of Nurses And Physicianscontrasting
confidence: 99%
See 1 more Smart Citation
“…The mean knowledge score for CRBSI prevention guidelines was very low for both nurses and physicians, although there was a significant difference in their mean scores with nurses performing better than physicians. This result contradicts the results of two studies conducted in Egypt, 12,30 which found low levels of knowledge for both physicians and nurses but with no significant difference between them. The explanation for this result might be that the nurses play an essential role in the daily care of CVC patients, while physicians are confined to CVC insertion in our selected hospitals.…”
Section: Differences In the Knowledge Level Of Nurses And Physicianscontrasting
confidence: 99%
“…11 The Centre for Disease Control and Prevention (CDC) publishes evidence-based guidelines to reduce and prevent the occurrence of CRBSI. 12 These recommendations are related to hand hygiene before puncturing the access, using intensive sterile precautions (cap, gown, mask, gloves), using 2% aqueous chlorohexidine and alcohol for skin preparation at the insertion site, and daily assessment and care. 13 Several studies have investigated and compared nurses and physicians' knowledge of CRBSI worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…16,18 Training in most of HD centers was found to rely on senior nurses who instruct and educate new staff members on protocols of CVCs care. 19 Although a formal training about updated infection control guidelines for CVCs maintenance and care is conducted every year by the Farwaniya hospital infection control team for the HD nurses, however only few number of nurses attend. Nurses at HD centers are usually busy and cannot leave the patient area for a longer period this is in addition to that infection control training sessions are always conducted during morning shifts.…”
Section: Resultsmentioning
confidence: 99%
“…The knowledge level and evidence based practices of HCWs regarding care and maintenance of different elements of CVCs in different settings has been assessed in many countries. 3,10,16,19,20 The studied elements related to care and maintenance of CVCs vary from study to another based on the study design (interventional, descriptive), population, aspects and settings. These variation does not create discrepancy in comparison, on the contrary it enriches the information gained from these researches and elucidate new elements for future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Another interventional study conducted in surgical and emergency ICUs at Zagazig University revealed the effectiveness of an education programme on knowledge, and improved practice of healthcare providers. Incidence of CRBSI decreased from 6.01/1,000 catheter-days to 3.9/1,000 catheter-days after the educational intervention (El Nemr et al, (2013). Taking into consideration the above facts the current study too intended to explore the impact of a well-designed self-instructional module on knowledge and the existing practices of nurses working in critical care areas with a view to reinforce better practices with regard to the prevention of central line–associated infection.…”
Section: Introductionmentioning
confidence: 99%